MANAJEMEN KEPEMIMPINAN DAN LEMBAGA DALAM PENDIDIKAN KEMENDIKBUDRISTEK, KEMENAG, DAN DIKTIS - Nining Huriati; Kasful Anwar; Shalahudin; Muhammad Taher; Titiek Prihatiningsih (EDU RESEARCH, 2024)
This article discusses leadership management and educational institutions under the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), the Ministry of Religious Affairs (Kemenag), and the Directorate General of Islamic Education (DIKTIS). The research aims to provide an overview of the roles and challenges faced by educational leaders, as well as strategies that can be implemented to enhance leadership effectiveness. The findings indicate that effective leadership is crucial for improving the quality of education in Indonesia.